2016
DOI: 10.3390/ijms17091579
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Analytical Considerations for Successful Next-Generation Sequencing (NGS): Challenges and Opportunities for Formalin-Fixed and Paraffin-Embedded Tumor Tissue (FFPE) Samples

Abstract: In cancer drug discovery, it is important to investigate the genetic determinants of response or resistance to cancer therapy as well as factors that contribute to adverse events in the course of clinical trials. Despite the emergence of new technologies and the ability to measure more diverse analytes (e.g., circulating tumor cell (CTC), circulating tumor DNA (ctDNA), etc.), tumor tissue is still the most common and reliable source for biomarker investigation. Because of its worldwide use and ability to prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 22 publications
2
54
0
Order By: Relevance
“…Despite the tested use of FFPE tissue in NGS [6], further studies are required to check whether archival FFPE samples are suitable for NGS [7,8]. A recent study found that FFPE samples stored for more than 7 years were not worth being included in NGS studies [9].…”
mentioning
confidence: 99%
“…Despite the tested use of FFPE tissue in NGS [6], further studies are required to check whether archival FFPE samples are suitable for NGS [7,8]. A recent study found that FFPE samples stored for more than 7 years were not worth being included in NGS studies [9].…”
mentioning
confidence: 99%
“…Over-fixation has been reported to cause excessive crosslinking, which interferes with the extraction of nucleic acids and proteins for NGS analysis. 18 On the other hand, under-fixation can lead to the degradation of nucleic acid and protein, or a change in gene expression in poorly perfused areas where the formalin has not reached. 18 Furthermore, fixation with formalin needs to be performed immediately after removal of the specimen to avoid ischemic changes in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…18 On the other hand, under-fixation can lead to the degradation of nucleic acid and protein, or a change in gene expression in poorly perfused areas where the formalin has not reached. 18 Furthermore, fixation with formalin needs to be performed immediately after removal of the specimen to avoid ischemic changes in the tissue. 18 Here, we have shown that high-quality DNA can be obtained as long as an appropriate preservation procedure is performed following a standard protocol with NBF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations